A study of the employee job satisfaction in respect of merging case of Bank Bumiputra Commerce Berhad / Khairulnakiah Sham - Sham, Khairulnakiah (Faculty of Business and Management, 2002)
Recently, job satisfaction among the employees becomes the most crucial subject in implementing the organizations progress. Due to that, this research is carried out on the job satisfaction among the employees in respect of merging case in Bank Bumiputra Commerce.